Formação e atuação interprofissional no Centro Pró-Sorriso da Universidade de Alfenas - Unifenas: Trabalho em equipe e educação interprofissional na atenção às deformidades craniofaciais: uma análise - Ferreira, Gustavo [UNIFESP] (2017)
Introduction: Craniofacial deformities present a complex situation with psychological, physiological and social consequences that require the intervention of a team with a variety of professionals, such as physicians, dental surgeons, nutritionists, psychologists, social workers, from the perspective of a team of one Collaborative Practice. In this context, it is impossible not to mention the Interprofessional Training for this practice. This modality of Innovative Curriculum, whether in undergraduate, postgraduate, continuing education or in permanent formation has been a challenge today. According to WHO, inter-professional education occurs when students from two or more professions learn about each other, with each other and with each other to enable effective collaboration and improve health outcomes. General objective: To investigate the process of formation and permanent education for the teamwork of teachers and students who work in the care of patients with craniofacial deformities with a view to collaborative practice and integral care. Specific objectives: To understand the conceptions of team work and collaborative practice of professionals who work on craniofacial deformities, to raise the difficulties experienced by professionals in their process of permanent education as a health team, and value the incorporation of Interprofessional Education (EIP) to the permanent education of the teams. Method: The study was qualitative and quantitative, of descriptive and exploratory nature, observing the ethical precepts. The research was carried out in two stages: first was the application of the Likert type Attitudinal Instrument where 36 professionals answered, being this one constructed with 3 dimensions based on the objectives of the study. The second step was semi-structured interviews with 15 professionals (a number that occurred due to saturation of information). Likert data were analyzed statistically and content of the interviews by content analysis, thematic modality and the later triangulated data. Results: Respondents, for the most part, agree with the effectiveness of Collaborative Teamwork and understand that this practice should be improved, with the need to intersect areas of professional activity in the daily life of its activities and with the importance of joint planning of actions, understanding that this point should be intensified. Faced with the difficulties experienced in the Permanent Education of the Team, a predominance of the multiprofessional approach of action is observed, the predominance of a multiprofessional permanent education model; The need for practices with protected schedules, training and interprofessional work and with innovative methodologies, existence of variables such as lack of time, few resources, individualism, lack of personal motivation that disrupt the EP of the team. In relation to Interprofessional Education, professionals confuse IPE with fragmented multiprofessional training, recognize the IPE as a training strategy that allows them to acquire a holistic profile of performance and leave more prepared to act in teams with a collaborative profile, perceive that IPE improves professional relationships, increases resolution, decreases costs, reduces stress, humanizes the professional / patient relationship. Conclusions: We hope that this study will subsidize intervention proposals, in a dialogical way, that allow the constant evolution of care for patients with craniofacial deformities, relationship with the community and similar institutions.